A Study of Indonesian Youth’s Semantic Perception of English Political Memes on ‘What Is Up, Indonesia?’ Instagram Account - Salwa Shabra Shatilla; Erni Erni; Mahdum Mahdum (Journal of Education and Learning Research, 2026)
Political memes have become a popular medium for conveying political messages on social media, particularly among young audiences. However, understanding such content requires the ability to interpret both explicit and implicit meanings. This study aims to examine Indonesian youth’s semantic perception of English political memes shared by the Instagram account What Is Up, Indonesia? (WIUI). Using a descriptive quantitative approach, the study involved 50 Indonesian youth aged 18–30 who actively use Instagram and are familiar with WIUI’s content. Data were collected through a 22-item questionnaire using a four-point Likert scale and analyzed using descriptive statistics. The findings indicate that respondents generally demonstrated a fairly good level of semantic perception. The highest understanding was observed in multimodal meaning and irony recognition, while clarity of meaning and evaluative perception showed greater variation. This study highlights the role of multimodal meaning in shaping interpretation and contributes to the limited research on how non-native English-speaking youth interpret political memes in digital contexts. Overall, English political memes can serve as an accessible medium for political communication among Indonesian youth.